Two new species of the echinoid genus Monostychia from the Miocene of Victoria and a redescription of M. etheridgei Tenison-Woods, 1877. Issue 2 (3rd April 2019) - Sadler, Tony; Holmes, Francis C.; Gallagher, Stephen J.
Abstract : Sadler, T., Holmes, F.C., & Gallagher, S.J., 8 January 2019. Two new species of the echinoid genus Monostychia from the Miocene of Victoria and a redescription of M. etheridgei Tenison-Woods, 1877. Alcheringa 43, 279–290. ISSN 0311-5518. Two new species of the clypeasteroid Monostychia Laube, 1869, are described; M. merrimanensis sp. nov. from the East Gippsland region of Victoria and M. glenelgensis sp. nov. from the Gambier Embayment of southwestern Victoria. M. etheridgei Tenison-Woods, 1877, from northern Tasmania, which closely resembles M. merrimanensis sp. nov., is redescribed. A comparison is also made between M. elongata Duncan, 1877, and M. glenelgensis, as both are present in the same strata. The new taxa differ from previously described Monostychia species in size and shape and in the number of post-basicoronal plates on the oral surface. It is concluded that the use of oral plate counts and their variation across a population may be diagnostically useful at species level, particularly those of the paired interambulacra and the unpaired ambulacrum III. Tony Sadler* [ t.sadler@student.unimelb.edu.au ] Earth Sciences, The University of Melbourne, Melbourne, 2010 Australia ; Francis C. Holmes [fholmes@bigpond.net.au ] Invertebrate Palaeontology, Museum Victoria, Melbourne, Victoria, 3001 Australia ; Stephen J. Gallagher [sjgall@unimelb.edu.au ] School of Earth Sciences, The University of Melbourne, Melbourne, 3010 Australia .